Peran trait mindfulness terhadap kesejahteraan psikologis pada lansia - Dyah, Ayu Suci Purnamaning; Fourianalistyawati, Endang (Konsorsium Psikologi Ilmiah Nusantara, 2018)
As individuals enter the elderly stage of development, they undergo many physical, social, spiritual, and psychological changes. Older adults who are not ready for the certain changes may be more susceptible to stress. Stressful conditions may reduce psychological well-being in the elderly. To deal with such issues, older adults need to have the ability to be aware of present experience, or is also called the trait mindfulness. This study attempted to see if the trait mindfulness has a significant role in psychological well-being. The sample of this research was retired older adults living in Jakarta, Bogor, Depok, Tangerang, and Bekasi (n = 120). This study used an adapted scale of the Five Facet of Mindfulness Questionnaire (FFMQ) to measure trait mindfulness and an adapted version of the Psychological Well-Being Scale to measure psychological well-being. Regression results indicate that four of the five dimensions of trait mindfulness have significant roles on some dimensions psychological well-being. Those dimensions of trait mindfulness are acting with awareness, describing, non reactivity, and non-judging. Observing is found not to have any significant role in psychological well-being.